Breech presentation induction compared to cephalic presentation: Effectiveness and characteristics. (March 2023) - Leblanc, Florence; Khobzaoui, Myriam; Cailliau, Emeline; Subtil, Damien; Houfflin-Debarge, Veronique; Garabedian, Charles; Ghesquière, Louise
Abstract: Introduction: The objective of our study was to compare the effectiveness of induction in cephalic presentations to that of breech presentations as well as the characteristics of the latter and the maternal-fetal morbidity and mortality. Material and methods: This was a single-center retrospective study carried out at the Lille University Hospital in the Jeanne de Flandre Maternity Hospital including all patients with a breech fetus for whom an induction was indicated beyond 37 weeks of gestation between January 2014 and December 2020. A matching was performed to include 2 cephalic presentations for one breech presentation. The primary outcome was successful induction defined by two things: passage into the active phase (cervical dilatation > 5 cm) and vaginal delivery. Results: 101 inductions of breech presentations were included and matched to 202 cephalic presentations. After adjustment by BISHOP score, there was no significant difference in the caesarean section rate between the two groups (25.7% in cephalic vs 33.7% in breech, OR 0.67 [CI95% 0.38–1.18]) or in the rate of transition to active phase (80.7% in cephalic vs 82.2% in breech, OR 1.26 [CI95% 0.65–2.44]). Post-partum blood loss was not significantly different between the two groups (14.4% in cephalic vs 12.9% in breech, OR 1.22 [CI95% 0.57–2.57]). Moderate neonatal acidosis was more frequent in the breech group (6, 4% in cephalic vs 15, 8% in breech, OR 3.04 [CI95% 1.38–6.71]). Conclusion: Induction of breech births beyond 37 weeks of gestation appeared to be as effective as induction of cephalic presentations. There was no difference in the rate of caesarean section and transition to active labor. Maternal morbidity was not increased.